1970
DOI: 10.1021/bi00806a004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dissolution of the membrane and preparation of photoreceptor subunits from Rhodopseudomonas spheroides

Abstract: An effective and optimal combination of three reagents commonly used for modifying the structure of proteins has been developed for causing quantitative dissolution of membrane structure. Alkaline solution, 1.5 Triton X-100, and 6 M urea at 0" for about 2 hr causes quantitative conversion of chromatophores from wild-type Rhodopseudomoms spheroides into Triton-protein complexes having particle weights of less than 200,000. No trap activity is lost as evidenced by light-induced absorbance and electron paramagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…They found that it could be observed in their reaction-center preparations from the R-26 mutant of R. spheroides after addition of sodium dodecyl sulfate, and presented evidence for iron separation under these conditions. We want to underscore the fact that, of the methods used to purify reaction-center or phototrap systems, the AUT procedure is the only one that: (a) completely dissociates all wild-type, mutant, green-plant, and algae systems tested; (b) results in sufficient dissociation to allow separation of nearly all iron-containing material; (c) allows observation of a reduced radical that may be from the primary electronacceptor molecule; and (d) gives a low particle weight prel)aration in which the antenna bacteriochlorophyll and carotenoids are still a functioning part of the complex (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that it could be observed in their reaction-center preparations from the R-26 mutant of R. spheroides after addition of sodium dodecyl sulfate, and presented evidence for iron separation under these conditions. We want to underscore the fact that, of the methods used to purify reaction-center or phototrap systems, the AUT procedure is the only one that: (a) completely dissociates all wild-type, mutant, green-plant, and algae systems tested; (b) results in sufficient dissociation to allow separation of nearly all iron-containing material; (c) allows observation of a reduced radical that may be from the primary electronacceptor molecule; and (d) gives a low particle weight prel)aration in which the antenna bacteriochlorophyll and carotenoids are still a functioning part of the complex (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Details for dissolution of chromatophores by the alkaline-urea-Triton method have also been given (1, 2). The original conditions (3% Triton X-100-6 M urea, pH 11.5) were modified by the addition of 1 RESULTS When alkaline urea-Triton (AUT) particles were subjected to column electrophoresis, phototrap activity was found to correspond very closely with bacteriochlorophyll absorbance, as measured at 875 nm ( Fig. 1) (3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are generally referred to as reaction center prep arations. Another pigment-protein complex which has been extensively studied and characterized (Loach et al, 1970a;1970b) is the so-called 'photoreceptor subunits' isolated from Rhodospirillum rubrum using alkaline, urea and Triton X-100. This unit retains a portion of the antenna pigments.…”
Section: Introductionmentioning
confidence: 99%